Children’s Autonomic Nervous System Reactivity Moderates the Relations between Family Adversity and Sleep Problems in Latino 5-Year Olds in the CHAMACOS Study - Alkon, Abbey; Boyce, W. Thomas; Neilands, Torsten B.; Eskenazi, Brenda (Frontiers in Public Health, 2017)
Sleep problems are common for young children especially if they live in adverse home environments. Some studies investigate if young children may also be at a higher risk of sleep problems if they have a specific biological sensitivity to adversity. This paper addresses the research question, does the relations between children’s exposure to family adversities and their sleep problems differ depending on their autonomic nervous system’s sensitivity to challenges? As part of a larger cohort study of Latino, low-income families, we assessed the cross-sectional relations among family demographics (education, marital status), adversities (routines, major life events), and biological sensitivity as measured by autonomic nervous system (ANS) reactivity associated with parent-rated sleep problems when the children were five years old. Mothers were interviewed in English or Spanish and completed demographic, family, and child measures. The children completed a 15-minute standardized protocol while continuous cardiac measures of the ANS (respiratory sinus arrhythmia (RSA), preejection period (PEP)) were collected during resting and four challenge conditions. Reactivity was defined as the mean of the responses to the four challenge conditions minus the first resting condition. Four ANS profiles, coactivation, coinhibition, reciprocal low RSA and PEP reactivity, and reciprocal high RSA and PEP reactivity, were created by dichotomizing the reactivity scores as high or low reactivity. Logistic regression models showed there were significant main effects for children living in families with fewer daily routines having more sleep problems than for children living in families with daily routines. There were significant interactions for children with low PEP reactivity and for children with the reciprocal, low reactivity profiles who experienced major family life events in predicting children’s sleep problems. Children who had a reciprocal, low reactivity ANS profile had more sleep problems if they also experienced major life events than children who experienced fewer major life events. These findings suggest that children who experience family adversities have different risks for developing sleep problems depending on their biological sensitivity. Interventions are needed for young Latino children that support family routines and reduce the impact of family adversities to help them develop healthy sleep practices.